PENGEMBANGAN MEDIA PEMBELAJARAN FISIKA BERBASIS ADOBE FLASH CS6 DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) - Rizki Bayu Aji; Norma Sidik Risdianto; Siti Fatimah (Kaunia: Integration and Interconnection Islam and Science, 2015)
This study is aimed to: (1) produce physics instructional media based on Contextual Teaching and Learning (CTL) approach using Adobe Flash CS6 for students at grade X at senior high school, (2) determine the quality of the media based on experts and teachers assessment, (3) determine the students’ response toward the media. This research is a development  of 4-D according to Thiagarajan Sammel and Sammel which consists of 4 main steps are constrained to develop stages, namely, (1) define phase (definition),  (2) design stages (planning), (3) develop stage (development). Data was collected using a set of questionnaire and then analyzed by descriptive quantitative technique. The results are: 1) Physics learning media based on CTL has been developed on the subject of static fluid using Adobe Flash CS6; 2) the media is categorized  as a Very Good based on expert and teachers assessment; 3) students as users gave a positive response  toward the media and 77.64% Agree at the limited testing and 79.61% Totally Agree at the field testing.